Airlines reservations data analysis system (ARDS) : case study : Ethiopian Airlines - Uganda - Kajungu, Dan K. (Kampala, 2000)
Dissertation (B.Stat.) - Makerere University, 2000
Includes bibliographical references (p. 39)
Keywords: Airlines -- Reservation systems -- Uganda